Pancasila Education as One of the Forms of National Character in the Global Era - Wahyuni, Dewi (LifeSciFi, 2024)
The era is increasingly advanced and the challenges are extraordinary. The impact is on the character of the community. As the shaper of the spirit of Pancasila, all parties are needed to be able to participate in the goals of the nation that instills Pancasila. The points of Pancasila reflect the formation of national character. Data was obtained using descriptive qualitative methods, namely by observation, documents from the library, photos, videos and YouTube shows that incorporate characters that are in accordance with Pancasila in addition to in-depth literature studies and interviews. Interviews are carried out by taking data using very in-depth interviews by grouping respondents into primary and secondary data. Data grouping must be detailed and the data must be analyzed well. Obtain data can be presented in the results and discussion, and certainly answers the title presented above. Analysis of character education embedded in Pancasila can tingrained and will be applied in everyday life, an attitude of religious spirit, honesty, discipline, independence, democracy, love of the country, respecting and respecting other people, caring for others, caring for the environment, an agile personality. In accordance with the 1945 Constitution, the soul must conform. Providing understanding to the community is not just about socializing but must go directly into the community. Behavior can be an example that good character will reflect a good nation.The form of character education described above will form a soul that loves the country.